Carotid atherosclerosis, silent ischemic brain damage and brain atrophy: A systematic review and meta-analysis. (15th November 2016) - Moroni, Francesco; Ammirati, Enrico; Magnoni, Marco; D'Ascenzo, Fabrizio; Anselmino, Matteo; Anzalone, Nicoletta; Rocca, Maria Assunta; Falini, Andrea; Filippi, Massimo; Camici, Paolo G.
Abstract: Background: The widespread use of brain imaging has led to increased recognition of subclinical brain abnormalities, including white matter hyperintensities (WMH) and silent brain infarctions (SBI), which have a vascular origin, and have been associated to a high risk of stroke, disability and dementia. Carotid atherosclerosis (CA) may be causative in the development of WMH, SBI and eventually brain atrophy. Aim of the present systematic review and meta-analysis was to assess the existing evidence linking CA to WMH, SBI and brain atrophy. Methods: The relation between CA and WMH, SBI and brain atrophy was investigated through the systematic search of online databases up to September 2015 and manual searching of references and related citations. Pooled estimates were calculated by random-effects model, using restricted maximum likelihood method with inverse variance weighting method. Results: Of the 3536 records identified, fifteen were included in the systematic review and 9 were found to be eligible for the meta-analysis. CA was significantly associated with the presence of WMH (Odds Ratio, OR 1.42, confidence interval, CI 1.22–1.66, p < 0.0001) and of SBI (OR 1.89, CI 1.46–2.45, p < 0.0001). No meta-analysis could be performed for the relation between CA and brain atrophy due to the lack of suitable studies. Conclusions: CA was found to be associated to WMH and SBI. While no causative association can be inferred from the available data, the presence of carotid plaque may be considered a significant risk factor for subclinical cerebral damage.